MiR‐138 Promotes Induced Pluripotent Stem Cell Generation Through the Regulation of the p53 Signaling123. (24th July 2012) - Ye, Dan; Wang, Guiying; Liu, Yang; Huang, Wenfei; Wu, Minjuan; Zhu, Songcheng; Jia, Wenwen; Deng, An‐Mei; Liu, Houqi; Kang, Jiuhong
Abstract: Induced pluripotent stem (iPS) cells, especially those reprogrammed from patient somatic cells, have a great potential usage in regenerative medicine. The expression of p53 has been proven as a key barrier limiting iPS cell generation, but how p53 is regulated during cell reprogramming remains unclear. In this study, we found that the ectopic expression of miR‐138 significantly improved the efficiency of iPS cell generation via Oct4, Sox2, and Klf4, with or without c‐Myc (named as OSKM or OSK, respectively), without sacrificing the pluripotent characteristics of the generated iPS cells. Exploration of the mechanism showed that miR‐138 directly targeted the 3′ untranslated region (UTR) of p53, significantly decreasing the expression of p53 and its downstream genes. Furthermore, the ectopic expression of p53 having a mutant 3′‐UTR, which cannot be bound by miR‐138, seriously impaired the effect of miR‐138 on p53 signaling and OSKM‐initiated somatic cell reprogramming. Combined with the fact that miR‐138 is endogenously expressed in fibroblasts, iPS cells, and embryonic stem cells, our study demonstrated that regulation of the p53 signaling pathway and promotion of iPS cell generation represent an unrevealed important function of miR‐138. STEM Cells 2012;30:1645–1654